Etos Kerja dan Korelasinya dengan Peluang dan Tantangan Profesionalitas Masyarakat Muslim di Era Modern - Mohammad Irham (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2012)
Based on writer observation, there are few works on work ethic. There is  no sole theory could explains all phenomena and how to make weak to become  stronger and better. Sometimes work ethic influenced by belief, like a religion.  Sometimes it is affected by economic growth in a community. As a complex  religion, Islam explains about work ethic in adequate manner. At least, this could  be understood through worship concept that poses unlimited meanings, which  work ethic is included in.